RISK MANAGEMENT FACTORS ON CLIENT ACCEPTANCE DECISIONS IN A BIG4 KAP - Mia Selvina (Universitas Airlangga, 2017)
This study aims to provide empirical evidence regarding the evaluation of risk management in a non-big 4 public accounting firm on client acceptance decisions. Risk management is divided into 3 broad categories, namely client business risk, audit business risk, and KAP business risk. The sample used in this study are clients who apply for audit services at a public accounting firm that are not included in Big 4 KAPs. audits, and audit fees.